Computer-aided conceptual aircraft design (CACAD) for transport aircraft - Vaziry-Zanjany , Mohammad Ali (F) (Cranfield University, 1996)
CACAD is capable to optimise the size, and configurations of turbofab-powered transport aircraft. The synthesis sizes aircraft from the low-capacity short range Fokker F-100 class to the long range medium-capacity Airbus A-340 class. It has an optimisation capability, with the objective function being direct operating cost in which, maintenance costs is extensively sub-divided according to ATA chapters. The objective of this report is to present the listing, the user's guide on how to run the program, as well as the description of the formulation used within the program. There are flow charts, table of nomenclatures included in this report. The floppy disc that contains the programme listings will be made available on request from the office of Department of Aerospace Technology, College of Aeronautics, Cranfield University, Cranfield, Bedford, UK, MK43 0AL